Religious extremism and terrorism in the Internet – space: the current challenges and Kazakhstan experience of counteraction (International relations and international law Journal, 2016)
The World Wide Web has the most operational information, as useful to society, and one that calls for undermining national security, violation of the integrity of the State. The principle of easy access to the network information provides a tremendous opportunities for unlimited spread of religious extremism. At present there is a great number of different blogs, forums, chat rooms, and other media applications on which supporters of extremism can freely express their ideology and recruit into their ranks new supporters. The provision of effective counteraction to religious extremism can only be achieved through the joint efforts of: government agencies, representatives of traditional religions and the scientific community. The authors noting the need of preventive work to eliminate Internet sites which are marked active advocacy ideology of extremism and terrorism, and called for the participation in the crimes of terrorist and extremist orientation against people of another religion or nationality. Considering the fact that the spread of a crime extremist ideology has become an urgent problem this time, the policy of the State government establishes legal and organizational basis to curb the manifestations of all forms of extremism under the laws of the Republic of Kazakhstan.
Keywords: Internet; information; national security; religious extremism; propaganda